1996
DOI: 10.1523/jneurosci.16-23-07447.1996
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor Activation Inhibits Neuronal Volume Regulation after Swelling Induced by Veratridine-Stimulated Na+Influx in Rat Cortical Cultures

Abstract: Neurons and glia experience rapid fluctuations in transmembrane solute and water fluxes during normal brain activity. Cell volume must be regulated under these conditions to maintain optimal neural function. Almost nothing is known, however, about how brain cells respond to volume challenges induced by changes in transmembrane solute flux. As such, we characterized the volume-regulatory mechanisms of cultured cortical neurons swollen by veratridine-stimulated Na+ influx. Exposure of cortical neurons to 100 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 54 publications
(62 reference statements)
5
51
0
Order By: Relevance
“…3 A, C,E). These results confirm and extend previous findings that established the presence of RVD in mouse cortical neurons challenged with hypotonic solution (Inoue et al, 2005) or the sodium channel activator veratridine (Churchwell et al, 1996). Notably, the homeostatic mechanisms are powerful because the neurons reestablished their original cell volume despite persistence of the osmotic stressor.…”
Section: Discussionsupporting
confidence: 91%
“…3 A, C,E). These results confirm and extend previous findings that established the presence of RVD in mouse cortical neurons challenged with hypotonic solution (Inoue et al, 2005) or the sodium channel activator veratridine (Churchwell et al, 1996). Notably, the homeostatic mechanisms are powerful because the neurons reestablished their original cell volume despite persistence of the osmotic stressor.…”
Section: Discussionsupporting
confidence: 91%
“…؊ channels activated during excitotoxic stimulation are involved in varicosity formation Although it was found that some volume-regulatory pathway is disrupted during activation of NMDA receptors in cortical neurons (Churchwell et al, 1996), we were able to consistently observe robust activity of the VSOR Cl Ϫ channel, which plays a volume-regulatory role in nonexcitotoxic swollen neurons (Inoue et al, 2005), on varicosities during NMDA receptor stimulation (Fig. 7).…”
Section: Neuronal Vsor CLmentioning
confidence: 75%
“…Each symbol represents the mean current Ϯ SEM (error bars). *At given voltages, data points designated with circles that were significantly different from those designated with squares at p Ͻ 0.05. toxic conditions, volume regulation was inhibited in cortical neurons (Churchwell et al, 1996). Thus, it is important to investigate the activity and roles of volume-regulatory Cl Ϫ channels in cortical neurons during and after an excitotoxic insult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under physiological conditions these two independent permeability pathways mediate electrically coupled loss of K + and Cl − , which is accompanied by an efflux of osmotically obligated water, and REGULATORY VOLUME DECREASE, or RVD [30,33,34]. However, in pathology, anoxic and/or glutamate-driven depolarization disrupts cell volume regulation due to an inhibition of the Na + ,K + -pump, dissipation of K + and Cl − electrochemical gradients, and blockade of volume regulatory channels [13,21,25,35]. Na + begins to accumulate uncontrollably in the cells via leak mechanisms, voltage-gated Na + channels, and other Na + -transporting pathways, which are considered in following sections.…”
Section: Introduction: Overview Of Ischemic Brain Damagementioning
confidence: 99%